Evaluation of Anti-Urolithiasis Activity of Leucasaspera Byin Vitro Method - Chandrasekar Sabarinath; Senthilkumar Gayathridevi; Pachiappan Sudhakar; Venkatesan Sariga; Sekar Sneha; Muthusamy Gayathiri (Asian Journal of Pharmaceutical Research and Development, 2024)
Objective: Urolithiasis is the accumulation or development of stone in any component of urinary system including kidney, ureters and urinary bladder. The aim of the current research is to perform anti- urolithiasis activity of ethanolic extract of leucas aspera can be evaluated in vitro by utilize the nucleation assay, aggregation assay, growth assay and titrimetric method. Methods: The leaf of leucas aspera is subjected to ethanolic extract by cold maceration method. anti urolithiasis action can be evaluated in vitro by utilize the nucleation assay, aggregation assay, growth assay and titrimetric method. Results: The result of this study shows that an ethanolic extract of leucas aspera leaf may have therapeutic benefits for reducing of kidney stone through in vitro models. The study findings of nucleation assay shows that the extract and cystone also reduced the size and number of caox crystals. the percentage reduction in size of caox crystals obtained for the extract (60.57%) was comparable to that produced by cystone (62.97%). in growth assay, the percentage of reduction in growth in the presence of this fraction was found to be 79±2.2% comparable to that of cystone 82.7±2.6% at 1000µg/ml was demonstrated. Conclusion: The study findings indicate that leucas aspera ethanolic extract has anti urolithiasis capability when used in in-vitro methods. Mostly all extracts showed marked crystal size reduction and morphological modifications, thus ethanolic extract of leaf part of leucas aspera could be further analyzed and further characterization of its active compound lead to the discovery of a new drug for urolithiasis.